Fromm’s notion of spontaneity as a solution to Foucault’s problem of freedom - Domjanović, Luka (Array, 2019)
In this paper, I attempt to apply Fromm’s notion of spontaneity to Foucault’s system of repression. It tends to shed new light on Foucault’s problem of freedom, using the notion which Foucault largely underestimates. Difficulties of such an application arise because of differences in Fromm’s and Foucault’s starting points in analysing the causes of human submission throughout history. Nonetheless, there is a point of convergence: Foucault and Fromm both describe a type of individual’s escape towards the institutions of power. Whether these institutions are highly formalised or not, highly complex or rather simple, dispersed or centralised, they designate repression on account of their lack of spontaneity.